2006
DOI: 10.1002/bjs.5240
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal metastasis is an indicator of poor prognosis in patients with gastric carcinoma

Abstract: EM is an independent prognostic factor and should therefore be included in the tumour node metastasis (TNM) staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 15 publications
7
64
1
Order By: Relevance
“…The presence of extracapsular invasion (ECI) has been reported to be a signifi cant prognostic factor in patients with gastric cancer [3,6]. Recently, it has been suggested that perinodal involvement is related to advanced stage and appears to be a reliable prognostic factor for gastric cancer [7][8][9]. However, conclusive results have not been drawn from these previous reports because of their inclusion of heterogeneous tumor stages.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of extracapsular invasion (ECI) has been reported to be a signifi cant prognostic factor in patients with gastric cancer [3,6]. Recently, it has been suggested that perinodal involvement is related to advanced stage and appears to be a reliable prognostic factor for gastric cancer [7][8][9]. However, conclusive results have not been drawn from these previous reports because of their inclusion of heterogeneous tumor stages.…”
Section: Introductionmentioning
confidence: 99%
“…The former two are reasonable events in advanced-stage cancer; however, the mechanisms underlying scattered-type CSM remain unknown. Although some studies have shown scatteredtype CSM [2][3][4][5] in gastric cancer, it is not yet clear how scattered cancer cells infiltrate the surrounding tissue. How do cancer cells infiltrate the mesogastrium?…”
Section: Discussionmentioning
confidence: 99%
“…Such a pathological finding has not yet been unequivocally named or defined; however, it has been called perinodal cancer cell [2], extranodal metastasis [3], extranodal invasion [4][5], and extracapsular spread [1]. Recently, this pathological finding has been reported as an independent negative prognostic factor influencing postoperative survival in patients with gastric cancer [1][2][3][4][5]. Although the precise mechanisms underlying this type of cancer cell spread have not yet been fully understood, it has been suggested that such cancer cell spread may reflect part of the primary tumor, lymphatic/vascular vessel involvement, infiltration from metastatic lymph nodes, or peritoneal metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…If partial omentectomy is enough for some population of AGC, the hurdle for LS will be further reduced. However, several researchers insisted that in some metastatic nodes extra-nodal expansion is recognized, which means cancer cell spread out of lymph node capsule to the adjacent adipose tissue (4,5). This might be one of the rationales for performing omentectomy in AGC.…”
Section: Total Omentectomymentioning
confidence: 99%